Managing Inclusive Educational Infrastructure for Children with Autism Spectrum Disorder: A Qualitative Case Study in Early Childhood Education - Fahmi Syarifudin; Aan Komariah; Dedy Achmad Kurniady; Sururi Sururi; Rifky Aditya Ramadhan (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study examines the management of inclusive educational infrastructure in early childhood education for children with Autism Spectrum Disorder (ASD) at the EDUfa Autism Therapy Center. Using a qualitative case study design, the research investigates how physical learning environments are planned, utilized, and adapted to support children’s sensory, social, and learning needs. Data were collected through observations, semi-structured interviews with therapists, parents, and administrators, and document analysis, and were analyzed thematically. The findings reveal that EDUfa integrates educational and therapeutic functions through sensory-responsive classroom design, transition spaces, and life-skills-oriented facilities. Infrastructure management is characterized by adaptability, collaborative decision-making, and continuous evaluation involving multiple stakeholders. However, financial limitations and shortages of specialized personnel remain significant challenges. The study underscores that effective infrastructure management is central to inclusive, child-centered early childhood education and offers practical insights for institutions seeking to develop inclusive learning environments in resource-constrained contexts.